So similar and yet so different : a comparative analysis of a firm's cost and benefits of apprenticeship training in Austria and Switzerland - Moretti, Luca [Verfasser]; Mayerl, Martin [Verfasser]; Mühlemann, Samuel [Verfasser]; Schlögl, Peter [Verfasser]; Wolter, Stefan C. [Verfasser] (My University, 2017)
"The authors compare a firm's costs and benefits of providing apprenticeship training in Austria and Switzerland, using two original micro data sets. While both countries share a number of similarities, including an extensive vocational education and training (VET) system, and a common border, there are some important institutional differences. On average, a Swiss firm generates a net profit of 3400 Euro per apprentice and per year of training, while an Austrian firm incurs net costs of 4200 Euro. Applying matching models, we find that this difference is largely driven by a higher relative apprentice pay in Austria, which in turn is associated with collective bargaining agreements and competition with alternative school-based VET pathways. However, Austrian firms can still generate a return on their training investment, partly due to wage subsidies, but mostly by retaining a high share of apprentices as skilled workers, and thereby save on future hiring costs." (Authors' Abstract ; BIBB-Doku)
Keywords: G 1.3.1.1 Ausbildungsstellenmarkt; S 4.2 Kostenarten; I 2.2.1 Westeuropa; Ausbildungskosten; Ausbildungsvergütung; Kosten-Nutzen-Analyse; Internationaler Vergleich; Österreich; Schweiz